Hepatitis B virus infection and risk of non‐alcoholic fatty liver disease: A population‐based cohort study. (19th August 2018) - Zhu, Liguo; Jiang, Jie; Zhai, Xiangjun; Baecker, Aileen; Peng, Hong; Qian, Jiao; Zhou, MingHao; Song, Ci; Zhou, Yan; Xu, Jianfang; Liu, Hongjian; Hang, Dong; et al.
Abstract: Background & aims: Although non‐alcoholic fatty liver disease (NAFLD) has been studied extensively, the potential risk factors for NAFLD among chronic hepatitis B (CHB) patients have not been fully known. Methods: A population‐based cohort of adult CHB patients without a history of alcohol drinking or NAFLD were recruited and followed up from October 2012 to January 2015 in Jiangsu province, China. Using Cox proportional hazards regression model, potential risk factors including viral and metabolic factors for NAFLD were evaluated. Results: Two thousand three hundred and ninety‐three adult CHB patients (mean age 50.7 ± 13.2 years) were included in the cohort. With 4429 person‐years of follow‐up, 283 individuals progressed to NAFLD with an incidence rate of 63.89/1000 person‐years. Overweight and obese CHB patients had an increased risk of NAFLD (overweight adjusted hazard ratio [HR], 3.10; 95% CI, 2.29‐4.18; obese HR, 8.52; 95%CI, 5.93‐12.25) compared to normal weight carriers. The incidence of NAFLD was associated with concurrent type 2 diabetes mellitus (DM) (HR, 1.88; 95%CI, 1.15‐3.08). However, no associations between viral factors with NAFLD incidence rate were identified. In a subgroup of participants with concurrent type 2 DM, detectable HBV DNA levels were negatively associated with the development of NAFLD (HR, 0.37; 95%CI, 0.14‐0.98). There was super‐multiplicative interaction between BMI and gender with respect to incidence of NAFLD, with an ROR of 2.08 (95%CI, 1.02‐4.23). Conclusion: Metabolic factors play an important role in the presence of NAFLD among Chinese CHB patients. However, viral replication factors are not related to NAFLD except among those with concurrent type 2 DM.